A review of metal oxynitrides for photocatalysis. Issue 5 (9th February 2016) - Ahmed, Manan; Xinxin, Guo
Abstract : This review highlights the recent progress in the production of hydrogen using a metal oxynitride photocatalyst under visible light irradiation. Abstract : Photocatalytic hydrogen (H2 ) production represents a very promising but challenging contribution to a clean, sustainable and renewable energy system. Photocatalytic water splitting into hydrogen and oxygen is a method to directly convert solar energy into storable chemical energy, and has received considerable attention for use in large scale solar energy utilization because of its great potential for low cost and clean energy production. Developing efficient and cost-effective photocatalysts for water splitting is a growing need, and semiconductor photocatalysts have recently attracted more attention due to their stability and simplicity. Over the past few decades, various metal oxide photocatalysts for water splitting have been developed and their photocatalytic application studied under UV irradiation. To harness solar energy efficiently, a recent main concern has been the development of visible-light ( λ > 400 nm) active photocatalysts for water splitting. Metal oxynitrides are emerging materials that may exhibit the properties of both oxides and nitride. Metal oxynitride photocatalysts are of significant interest in the field of photocatalytic water splitting as the observed small band gaps lead to activity in the visible range. Titanium, tantalum, niobium, gallium and zirconium form important photocatalysts which show promise in visible light-driven photoreactions. Along with perovskite structures, development of double complex perovskite oxynitrides that are active under visible light are also reviewed. This review article provides a broad overview of the development of water-splitting photocatalysts for generating hydrogen, summarizing the current state of work with a focus on the recent progress in visible-light induced overall water splitting on oxynitride photocatalysts.